Axitinib for the treatment of metastatic renal cell carcinoma. (February 2016) - Parekh, Hiral; Griswold, Julianne; Rini, Brian
Renal cell carcinoma is a cancer that results from a genetic inactivation of the VHL tumor suppressor gene leading to an upregulation of VEGF. Targeted therapies against VEGF receptors have piqued substantial interest among clinicians and researchers, and these drugs are now the standard of care in the treatment of advanced renal cell carcinoma. One of these VEGF receptor inhibitors, axitinib, has been shown to be a superior second-line therapy when compared with sorafenib. Although axitinib has clinical activity and a manageable safety profile in patients with treatment-naive metastatic renal cell carcinoma, utility in the front-line setting is area of ongoing investigation. Another area of ongoing research is dose titration of axitinib to achieve the maximum clinical benefit. Interestingly, the axitinib-related side effect of hypertension has shown to be associated with more favorable clinical outcomes. This article describes the development of axitinib and discusses the current indications for clinical use in the management of metastatic renal cell carcinoma.